ANALISIS AGLOMERASI INDUSTRI, PENGANGGURAN, DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP PDRB KABUPATEN/KOTA DI PROVINSI JAWA BARAT TAHUN 2017-2021 - Ilham Ariviandi Gunarto (Jurnal Pendidikan Ekonomi Indonesia, 2023)
This study aims to analyze the effect of the Industrial Agglomeration, Unemployment, and Human Development Index on the GRDP of Regencies/Cities in West Java Province in 2017-2021. Research method to determine the relationships between variables using panel data analysis. The data used in this study is secondary data in 27 Regencies/Cities in West Java Province obtained from the Central Bureau of Statistic and Opendata West Java with the help of Eviews 10 Software. This study used multiple linear analysis with the REM (Random Effect Modell. The results of this study show that industrial agglomeration and Human Development Index have a significant positive effect on the Gross Regional Domestic Product of Regencies/Cities in West Java Province, while unemployment has an insignificant positive effect on the Gross Regional Domestic Product of Regencies/Cities in West Java Province.